The Effect of the Great Arab Revolution on the Political Speech of King Hussein Bin Talal "1953-1999" - Al-bree, Hayel (Dirasat: Human and Social Sciences, 2020)
The aim of this study is to show the effect of the Great Arab Revolution on the political Speech of King Hussein Bin Talal, he is the third king of bani Hashim’s kings who took over the thrown of the Hashemite kingdom of Jordan. His upbringinghas it’s effect on understanding the idea and reasons of the Arab Revolution. This revolution was present in his mind and he follows the methodology of its leader in preparation and constructions. This study arrives at the fact that the Great Revolution has its effect on the thoughts and ideas of Al Hussein in different fields (political, economical, social, cultural, etc.), and on all directions, patriotic, national, and Islamic. All are applied to serve Arab and Islamic nations. He has achieved a revival in the Jordanian Arab people. He deals with building Jordan State in the spirit of the Great Arab Revolution. And reserved that during his regime, and strengthen the relation with his surrounding Arab and national world without violating his promises. He hadn’t failed to do his job to support Arab, he was interested to do so within Arab community since it enhances Arab situation and achieve development and civilization. Al Hussein was interested in united Arab world in many aspects such as the political and the economical since Arab has the same history, language, religion, culture and future.